Identifying Aboriginal and Torres Strait Islander offenders and victims in judicial sentencing remarks - Clifford, Sarah; Griffiths, Kalinda E. (Journal of criminology (2021), 2023)
Judicial Sentencing Remarks (JSRs) have been utilised by several researchers, as a publicly available data source, to explore topics such as alcohol and other drug involvement in intimate partner homicide; the use of therapeutic jurisprudence; narratives of mitigation for Aboriginal offenders; and the identification and impact of trauma in the sentencing of homicide offenders (to name a few). There is inconsistency in the existing literature regarding the methodology for identifying offenders as Aboriginal and/or Torres Strait Islander. Appropriate and correct identification of Aboriginal and Torres Strait Islander peoples in the criminal justice system is important because of the distinct differences in how Aboriginal and Torres Strait Islander peoples experience the criminal justice system, including sentencing and punishment. We retrospectively developed a manual algorithm to identify offenders and victims as "Aboriginal and/or Torres Strait Islander", "non Aboriginal and/or Torres Strait Islander" or "Unknown". This paper provides an overview of the development and the application of the algorithm and discusses the importance of transparency in Aboriginal and Torres Strait Islander identification processes when using JSRs as a data source.